Modeling of Temperature Field Distribution in Mine Dumps with Spread Prediction - Machacek, Z.; Hajovsky, R. (Elektronika ir Elektrotechnika, 2013)
The paper describes mathematical modeling and computation of thermal processes in the environment of mine dumps and industrial waste dumps. The developed program enables testing of various modeling methods and prediction of temperature field distribution and endogenous fires in mine dumps. It is possible to obtain enough information to design a mathematical model for spread prediction and possible dangerous endogenous fires from long time measurements of temperature fields below and above the surface. The present methodology is implemented in Matlab mathematical software environment, which enables the design of data files processing and implementation of algorithms for simulation of the temperature field in environment. DOI: http://dx.doi.org/10.5755/j01.eee.19.7.5179